Analysis of the Role of Communication Competence, Credibility, and Information Quality Of The “Tanya” Chatbot on Tokopedia Consumers’ Purchase Intention: A Mediating Approach Through User Satisfaction in the Era of Smart E-Commerce - Diajeng Mustika Rany; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of digital technology has driven the adoption of chatbots as one of the innovations in customer service within e-commerce platforms. Tokopedia, as one of Indonesia’s leading e-commerce platforms, introduced the chatbot “TANYA” to enhance user experience. However, the effectiveness of chatbots in influencing users' purchase intention remains a question, considering various factors that may affect online purchase decisions. Therefore, this study examines the influence of communication competence, information quality, and credibility on purchase intention, with satisfaction as a mediating variable among Tokopedia chatbot users. This research employs a quantitative method using a survey approach with 195 respondents who are users of the “TANYA” chatbot on Tokopedia. Data analysis was conducted using PLS-SEM with SmartPLS software. The results indicate that communication competence, credibility, and satisfaction positively and significantly affect purchase intention, while information quality positively affects satisfaction. Furthermore, satisfaction is proven to mediate the relationship between information quality and purchase intention. This study contributes to enriching the digital marketing literature on the effectiveness of chatbots in shaping consumer satisfaction and purchase intention. It also provides managerial implications for e-commerce platform managers in optimizing chatbot features to increase purchase transactions.